If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6y = 348 Solving 6x + 6y = 348 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 6x + 6y + -6y = 348 + -6y Combine like terms: 6y + -6y = 0 6x + 0 = 348 + -6y 6x = 348 + -6y Divide each side by '6'. x = 58 + -1y Simplifying x = 58 + -1y
| x-0.20=56 | | 5x-15=5x-15 | | 111=-3(5+6x) | | .25x+x=3800 | | 87=3(-3x+8) | | 4x(x+4)=9 | | 3n+5-4n=-22 | | 6x-21=33+10x | | 30x+65y=5840 | | -2(7k+9)=25 | | =95-2 | | 2(3x-10)=1 | | 4x+12x=-2254 | | -8(3+9a)=-20 | | 6(3x-10)=46 | | 5(3x-10)=46 | | 4(3x-10)=46 | | 3(3x-10)=46 | | 1(3x-10)=46 | | 12x-25=-63+7x | | 3(-2x+5)=12-4x | | -8x+4=-2(4x-2) | | -y=12-6x | | -20=2y-4 | | monkey+hat=toad | | 6x-y=12fory | | 8x+4=-2(4x-2) | | G=(x+y)(ax+bxy) | | ln(4-x)+ln(2)=2ln(x) | | G=ax(x+y)+bxy(x+y) | | 5w+10=5w+10 | | -19x-34=56+x |